A New Seven Level Symmetrical Inverter with Reduced Switch Count - Thiyagarajan V.; Somasundaram P. (Institute of Advanced Engineering and Science, 2018)
Multilevel inverters offers less distortion and less electro-magnetic interference compared with other conventional inverters and hence, it can be used in many industrial and commercial applications. This paper analyze the performance of the modified single phase seven level symmetrical inverter using minimum number of switches. The proposed topology consists of six switches and two dc sources, and produces seven level output voltage waveform during symmetric operation. The cost and size of the propsoed inverter minimum as it uses minimum number of components, The performance of the proposed multilevel inverter is analysed for different switching angles and the corresponding simulation results are presented. The simulation of the proposed inverter is carried out using MATLAB/Simulink software.